Metal Forming : mechanics and metallurgy - Hosford, William F.; Caddell, Robert M. (New York : Cambridge University Press, 2011)
'This book helps the engineer understand the principles of metal forming and analyze forming problems--both the mechanics of forming processes and how the properties of metals interact with the processes. In this third edition, an entire chapter has been devoted to forming limit diagrams and various aspects of stamping and another on other sheet forming operations. Sheet testing is covered in a separate chapter. Coverage of sheet metal properties has been expanded. Interesting end-of-chapter notes have been added throughout, as well as references. More than 200 end-of-chapter problems are also included'--
Machine generated contents note: 1. Stress and strain; 2. Plasticity; 3. Strain hardening; 4. Plastic Instability; 5. Temperature and strain-rate dependence; 6. Work balance; 7. Slab analysis and friction; 8. Friction and lubrication; 9. Upper-bound analysis; 10. Slip-line field analysis; 11. Deformation zone geometry; 12. Formability; 13. Bending; 14. Plastic anisotropy; 15. Cupping, redrawing and ironing; 16. Forming limit diagrams; 17. Stamping; 18. Hydroforming; 19. Other sheet forming operations; 20. Formability tests; 21. Sheet metal properties.
Includes bibliographical references and index.
Keywords: Metal-work.; Deformations (Mechanics); Metals -- Plastic properties